Can The Unsophisticated Market Provide Discipline? - Caprio, Gerard; Honohan, Patrick (World Bank, Washington, D.C., 2013)
The authors question the widespread belief that market discipline on banks cannot be effective in less developed financial environments. There is no systematic tendency for low-income countries to lack the prerequisites for market discipline. Offsetting factors to the weaker market and formal information infrastructures are (1) the less complex character of banking business in low-income countries; (2) the growing internationalization of these markets through the presence of foreign banks, and through international trading of the debt and equity of locally-controlled non-government banks; and (3) the smaller size of the business and financial community. However, continuing dominance by public sector banks in some countries limits the likely development of market monitoring, which is clearly a cause for concern, given the disappointing record of governments around the world as monitors of their self-owned banks. Countries should build on this potential for market discipline by limiting the role of explicit deposit guarantees, reducing state ownership of banks where it is prevalent, and not putting all their eggs in the supervisory basket. Greater disclosure, for example, of how risk taking is rewarded and how rating agencies earn their fees would support the development of better market monitoring. Enhancing market discipline (pillar three) is much more likely to be of use in most developing countries than addressing the refinements of the risk-weighting system of Basel II's first pillar.